Resilient Control Algorithm for Wind-Hydro Based Distributed Generation System with Grid Synchronization Capability - Sharma, Rohini; Singh, Bhim (2021 IEEE 4th International Conference on Computing, Power and Communication Technologies (GUCON), 2021)
Microgrid is a key to an efficient and resilient power grid operation. Thus in this paper, a robust control scheme is implemented namely modified frequency locked loop (MFLL), proficient in eliminating the voltage and current fluctuations because of phase/frequency variation. Therefore, enhancing the consistency of the supply across nonlinear load through a smooth transition from utility-interactive to islanded mode. It also achieves accelerated convergence and reduced steady-state error. MFLL is an easy control technique, with only one interfacing voltage source converter, which delivers a stable supply to critical loads during different operating modes. The implemented system has the main advantage of the capability of power-sharing between distributed generations (DGs) systems while regulating the voltage at the DC link. It also provides power quality improvement through harmonics suppression; voltage regulation during contingencies like unbalance in load and compensation in reactive power at the common coupling point following the prerequisite of the system. The performance through the implemented control algorithm is brought about in MATLAB 15b/Simulink platform. The performances of results are compared with already reported control strategies. Thus, simulated results comparison with existing work presents the competence of the implemented control strategy under dynamic conditions.